The Local and Systemic Humoral Immune Response Against Homologous and Heterologous Strains of the Type 2 Porcine Reproductive and Respiratory Syndrome Virus - Kick, Andrew R.; Amaral, Amanda F.; Frias-De-Diego, Alba; Cortes, Lizette M.; Fogle, Jonathan E.; Crisci, Elisa; Almond, Glen W.; Käser, Tobias (Frontiers in Immunology, 2021)
The humoral immune response plays a crucial role in the combat and protection against many pathogens including the economically most important, highly prevalent, and diverse pig pathogen PRRSV. In addition to viremia and viral shedding analyses, this study followed the local and systemic humoral immune response of pigs to one of three Type-2 PRRSV (PRRSV-2) strains – one modified live virus (MLV) vaccine strain, and two lineage 1 PRRSV-2 strains, NC134 and NC174. The local response was analyzed by quantifying immunoglobulin (Ig)A in nasal swabs. The systemic response was studied by the quantification of IgG and homo- and heterologous neutralizing antibodies (NAs). In all PRRSV-2 inoculated groups, viral nasal shedding started at 3 and peaked 3-7 days post inoculation (dpi); it was cleared at 28-35 dpi with sporadic rebounds thereafter. The local IgA response started 4-7 days after viral shedding with peaks at 14 dpi and at 28-35 dpi. The NC134 and NC174 strains induced a stronger local IgA response. As reported earlier, main viremia lasted from 7 dpi to 28 dpi (NC174), 42 dpi (NC134) or until the end of the study (MLV). Similar to the local IgA response, the systemic IgG response started 4-7 days after viremia; but in contrast to viremia, serum IgG levels stayed high for all PRRSV-2 inoculated groups. A significant finding was that while the serum NA response in the MLV group was delayed by 28 days, serum NAs in pigs infected with our two NC134 and NC174 strains could be detected as early as 7 dpi (NC134) and 14 dpi (NC174). Compared to homologous NA responses, the NA responses against heterologous strains was strong but slightly delayed between our lineage 1 strains or non-existent between the MLV and lineage 1 strains. This study improves our understanding of the relationship between local and systemic infections and the humoral immune response induced by PRRSV-2 infection or MLV vaccination. Our data also provide novel insights into the timeline of the development of homologous and heterologous NA levels – by both MLV vaccination or infection with two strains from the currently prevalent PRRSV-2 lineage 1.